2021
DOI: 10.1073/pnas.2110166119
|View full text |Cite
|
Sign up to set email alerts
|

Hemochromatosis drives acute lethal intestinal responses to hyperyersiniabactin-producing Yersinia pseudotuberculosis

Abstract: Hemachromatosis (iron-overload) increases host susceptibility to siderophilic bacterial infections that cause serious complications, but the underlying mechanisms remain elusive. The present study demonstrates that oral infection with hyperyersiniabactin (Ybt) producing Yersinia pseudotuberculosis Δfur mutant (termed Δfur) results in severe systemic infection and acute mortality to hemochromatotic mice due to rapid disruption of the intestinal barrier. Transcriptome analysis of Δfur-infected intestine revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…However, direct evidence regarding iron regulating neutrophils recruitment and inflammation is scarce. Published studies showed that interactions between iron and neutrophils is a pathological consequence of different types of disease ( 34 , 36 38 ). To the best our knowledge, the mechanism of iron regulating neutrophils recruitment and inflammation is most likely the chemokines secreted by certain types of cells influenced by iron, which means that the whole process is regulated by iron indirectly ( 34 , 36 38 ).…”
Section: Iron Regulates Neutrophils Recruitment and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, direct evidence regarding iron regulating neutrophils recruitment and inflammation is scarce. Published studies showed that interactions between iron and neutrophils is a pathological consequence of different types of disease ( 34 , 36 38 ). To the best our knowledge, the mechanism of iron regulating neutrophils recruitment and inflammation is most likely the chemokines secreted by certain types of cells influenced by iron, which means that the whole process is regulated by iron indirectly ( 34 , 36 38 ).…”
Section: Iron Regulates Neutrophils Recruitment and Inflammationmentioning
confidence: 99%
“…Published studies showed that interactions between iron and neutrophils is a pathological consequence of different types of disease ( 34 , 36 38 ). To the best our knowledge, the mechanism of iron regulating neutrophils recruitment and inflammation is most likely the chemokines secreted by certain types of cells influenced by iron, which means that the whole process is regulated by iron indirectly ( 34 , 36 38 ). In necrotizing fasciitis, keratinocyte-secreted hepcidin promotes CXCL1 production, thus promoting neutrophils recruitment.…”
Section: Iron Regulates Neutrophils Recruitment and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the gene expressions of IFN‐γ increased in postmortem fish muscle (Tie et al ., 2022b), supporting our hypothesis. Study showed that the inhibition of myosin light chain kinase (MLCK) phosphorylation could attenuate the disruption of structural integrity (Cao et al ., 2013), while the increased expression of MLCK could disrupt the tight junctions by regulating the TJ proteins (Das et al ., 2022). The present research showed the increased gene expressions of MLCK, indicating that postmortem fish muscle was involved with the increased disruption of integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Iron ions play an important role in immunity and can regulate the functional transformation of macrophages, neutrophils, NK cells, T cells, and B cells. The specific performance is to promote the conversion of macrophages to M1 type; promote the recruitment of neutrophils; maintain the function of NK cells; promote the differentiation of T cells; and promote the proliferation of B cells [143][144][145][146][147]. Therefore, the immune response can explain the synergistic effect between ferroptosis and PDT, which is a promising antitumor strategy.…”
Section: Sun Et Al Invented a New Type Of Photosensitizer Sr780mentioning
confidence: 99%